The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1080/20002297.2019.1710953
|View full text |Cite
|
Sign up to set email alerts
|

Integrated hypothesis of dental caries and periodontal diseases

Abstract: This review considers an integrated hypothesis of dental caries and periodontal diseases that builds on theoretical ecological principles. The backbone of the hypothesis is based on the dynamic stability stage of the oral microbiota, at which intrinsic (mainly saliva and gingival crevicular fluid) and bacterial (mainly metabolic) resilience factors maintain ecological dynamic stability, compatible with clinical health. However, loss of intrinsic resilience factors and/or prolonged changes in the availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 108 publications
(134 reference statements)
12
112
0
4
Order By: Relevance
“…ecological characteristics such as conditions of anaerobiosis and chronic in ammation being present in the local periodontal environment [34,35]. Taken together with a recent theory suggesting that frequent carbohydrate consumption may induce in ammation in the periodontal tissues [36], our nding that periodontitis as perturbation impairs carbohydrate metabolism of the plaque microbiota, provides a possible explanation as to why excessive carbohydrate intake may contribute to the pathogenesis of periodontitis. Interestingly, periodontitis is linked with medical disorders such as type 2 diabetes, with conditions of systemic low-grade in ammation as the immediate communality [37].…”
Section: Discussionmentioning
confidence: 60%
“…ecological characteristics such as conditions of anaerobiosis and chronic in ammation being present in the local periodontal environment [34,35]. Taken together with a recent theory suggesting that frequent carbohydrate consumption may induce in ammation in the periodontal tissues [36], our nding that periodontitis as perturbation impairs carbohydrate metabolism of the plaque microbiota, provides a possible explanation as to why excessive carbohydrate intake may contribute to the pathogenesis of periodontitis. Interestingly, periodontitis is linked with medical disorders such as type 2 diabetes, with conditions of systemic low-grade in ammation as the immediate communality [37].…”
Section: Discussionmentioning
confidence: 60%
“…Nutrition can influence the oral biofilm composition and thus, the onset of oral diseases. Specifically, the content of fermentable carbohydrates is crucial in the process of cariogenic demineralisation [21]. However, recent studies also showed an influence of sugar on gingival inflammation which might be etiologically related to both local and systemic effects like elevated blood sugar [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Modern life, regular healthy diet, and sugar consumption affect the oral microbiome resulting in a dysbiosis which disturbs the ecologically balanced biofilm that can cause diseases in the oral or other tissues. 24,25 For example, periodontal disease can increase the risk of diabetes [26][27][28] , and musculo-tendinous overuse injuries are prevalent in people with type 2 diabetes. 29 Periodontal disease has been shown to impair muscle recovery in an animal experimental model.…”
Section: Periodontal Diseasementioning
confidence: 99%